Comparing Self-Directed Online Learning Between Nursing and Non-Nursing Students During Novel Corona Virus-2019 Pandemic in Indonesia: A National Web-Based Survey - T Taryudi; Linlin Lindayani; Irma Darmawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
A novel coronavirus outbreak (2019-nCoV) caused all universities to work online and all students study from home to control the transmission of 2019-nCoV. This study investigated self-directed online learning among university student during the corona virus-2019 pandemic in Indonesia. A web-based survey was conducted to collect data using the Self-Directed Learning Instrument (SDLI). A total of 793 respondent (response rate: 98.5%) joined in this study. Over 70% of students experienced difficulty using a learning management systems. The mean total of self-directed learning was significantly higher in nursing students than non-nursing students (78.75±9.66 vs. 77.35±8.06, p-value=0.008, respectively). Both groups showed the highest percentage of perception of successes and failures inspire me to continue learning (90%) and having strong hope to constantly improve and excel in their learning (86%).  It’s very important for the university to develop a better e-learning system and design intervention to improve students’ self-directed learning.  Abstrak: Wabah coronavirus baru (2019-nCoV) menyebabkan semua universitas bekerja online dan semua siswa belajar dari rumah untuk mengendalikan penularan 2019-nCoV. Penelitian ini menyelidiki pembelajaran online mandiri di kalangan mahasiswa saat terjadi pandemi virus corona 2019 di Indonesia. Survei berbasis web dilakukan untuk mengumpulkan data menggunakan Self-Directed Learning Instrument (SDLI). Sebanyak 793 responden (tingkat tanggapan: 98,5%) bergabung dalam penelitian ini. Lebih dari 70% siswa mengalami kesulitan untuk menggunakan sistem manajemen pembelajaran. Rata-rata total pembelajaran mandiri secara signifikan lebih tinggi pada mahasiswa keperawatan daripada mahasiswa non-keperawatan (78,75±9,66 vs 77,35±8,06, p-value=0,008, masing-masing). Kedua kelompok menunjukkan persentase tertinggi dari persepsi keberhasilan dan kegagalan menginspirasi saya untuk terus belajar (90%) dan memiliki harapan yang kuat untuk terus meningkatkan dan unggul dalam pembelajaran mereka (86%). Sangat penting bagi universitas untuk mengembangkan sistem e-learning yang lebih baik dan merancang intervensi untuk meningkatkan pembelajaran mandiri siswa.